(untitled) - Green, Roger (Jakarta Pusat, Indonesia, 1987)
1. General introduction, 2. Introduction to hardware & software systems, 3. Introduction to linear regression, 4. Nonlinear relationships
Keywords: Sinh học môi trường,Environmental biology